2021
DOI: 10.7554/elife.67718
|View full text |Cite
|
Sign up to set email alerts
|

Functional interdependence of the actin nucleator Cobl and Cobl-like in dendritic arbor development

Abstract: Local actin filament formation is indispensable for development of the dendritic arbor of neurons. We show that, surprisingly, the action of single actin filament-promoting factors was insufficient for powering dendritogenesis. Instead, this required the actin nucleator Cobl and its only evolutionary distant ancestor Cobl-like acting interdependently. This coordination between Cobl-like and Cobl was achieved by physical linkage by syndapins. Syndapin I formed nanodomains at convex plasma membrane areas at the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…The defects caused by MCAO in pyramidal neurons in cortical layers II/III and V of the murine M1 seemed somewhat related to those observed for Cobl loss of function in immature rat hippocampal neurons in culture [ 30 , 34 ]. We therefore addressed whether Cobl may also play some important role in shaping cortical neurons and whether furthermore Cobl may not only do so in developing neurons in culture but also in adult neurons in the cortex of mice with a demand for remapping neuronal circuits subsequent to stroke.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The defects caused by MCAO in pyramidal neurons in cortical layers II/III and V of the murine M1 seemed somewhat related to those observed for Cobl loss of function in immature rat hippocampal neurons in culture [ 30 , 34 ]. We therefore addressed whether Cobl may also play some important role in shaping cortical neurons and whether furthermore Cobl may not only do so in developing neurons in culture but also in adult neurons in the cortex of mice with a demand for remapping neuronal circuits subsequent to stroke.…”
Section: Resultsmentioning
confidence: 98%
“…Indeed, Cobl functions require arginine methylation of one of its 3 G-actin binding WH2 domains by the arginine methyltransferase PRMT2 [ 35 ]. Furthermore, Cobl’s N terminal membrane-associating domain (the Cobl Homology domain) interacts with syndapin I in a Ca 2+ /CaM-regulated manner in early neuromorphogenesis [ 36 ] and links Cobl to its functional partner Cobl-like [ 34 ]. Strikingly, also Cobl’s actin nucleating, WH2 domain-containing C-terminal part was found to be controlled by association of Ca 2+ -activated CaM [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial membrane insertion as molecular mechanism of Ankrd26’s membrane binding suggested that it might be possible to establish a detection of endogenous Ankrd26 in cellular membranes by freeze- fracturing, immunogold labeling and transmission electron microscopy (TEM) similar to methods, which we were able to successfully establish for other membrane-inserted proteins, such as caveolins (Koch et al, 2012; Seemann et al, 2017), syndapins (Schneider et al, 2014; Seemann et al, 2017; Izadi et al, 2021), and the N-Ank protein ankycorbin (Wolf et al, 2019). Freeze-fractured plasma membranes of SK-N-SH neuroblastoma cells differentiated with retinoic acid and BDNF according to Encinas et al (2000) were successfully immunogold labeled with antibodies against Ankrd26 ( Figure 3N ).…”
Section: Resultsmentioning
confidence: 99%
“…SK-N-SH cells (RRID:CVCL_0531) were cultured on poly-D-lysine-coated coverslips in 24-well plates and were differentiated by adding 10 µM all-trans retinoic acid (Sigma; R2625) on day 2 and conducting a media exchange to brain-derived neurotrophic factor (BDNF)-containing media (DMEM with 50 ng/ml BDNF, PreproTech; 080861) at day 5. At day 8, cells were transfected using TurboFect as described before (Haag et al, 2018; Izadi et al, 2021). Prior to fixation two days later, cells were washed with PBS and incubated with 0.05% (w/v) tetramethylrhodamine-coupled wheat germ agglutinin (WGA) (Molecular Probes) in PBS for 30 min at RT.…”
Section: Methodsmentioning
confidence: 99%